Fracture properties on the adhesive interface of double cantilever beam specimens bonded with lightweight dissimilar materials at opening and sliding modes. (1st October 2020) - Kim, J.W.; Cho, J.U.
Abstract: This study aims at investigating the fracture properties of double cantilever beam (DCB) by the combination of lightweight materials at opening and sliding modes. The specimens were prepared by referring to the British Standard of BS7991. In terms of experimental conditions, the lower part was fixed while the enforced displacement of 3 mm/min was applied to the upper part at both opening and sliding modes. As a result of the experiment, the maximum reaction forces at the opening mode and the sliding mode were seen to be highest in the order of CFRP-Al, Al–Al_Foam and CFRP-Al_Foam. At the opening mode, the maximum energy release rate was found to be in the order of Al–Al_Foam, CFRP-Al and CFRP-Al_Foam. In the sliding mode, the maximum energy release rate was found to be in the order of CFRP-Al, Al–Al_Foam and CFRP-Al_Foam. In the opening mode, the maximum reaction force of about 1.5 mm was shown at the composite specimens with CFRP. At the composite specimen with Al, it can be seen that the maximum reaction force happens at about 0.7 mm, and a rapid rise or drop takes place at this point. The brittleness at mode I is mostly likely to be the fracture property of adhesive. By considering the reaction force and energy release rate, the strain energy became relatively large among the specimens of CFRP-added combination in the sliding mode.